Chapter Introduzione. Umberto Gori e le Relazioni Internazionali in Italia - CESA, MARCO (Studi e saggi, 2022)
Umberto Gori has held the first chair of International Relations in Italy and has been the first scholar to address a series of central topics in the analysis of foreign policy and international politics. Those who browse, even if only rapidly, his rich bibliography cannot but be struck by the great variety of the topics examined: from the first works of a predominantly legal nature, we move on to studies centered on methodological and epistemological issues, relations between states, analysis of foreign policy in general and Italian foreign policy in particular, Peace Research, strategic affairs, intelligence, and finally the impact of the information and digital revolution on international politics and contemporary strategy. What holds together so many different issues is, firstly, a constant attention to methodology and, secondly, a clear preference for a predominantly operational approach, in the belief that knowledge must always be functional to decision and action. These basic attitudes are reflected not only in his strongly characterized research agenda, but also in the twofold nature of his teaching commitment: on the one hand, Gori taught outside the university classrooms, at military and governmental institutions, for decades; on the other hand, he introduced issues traditionally reserved to diplomacy and security institutions into the Italian academic context. Such a propensity to build bridges between different worlds - academic, military, technological, diplomatic, financial - and a research vocation that has never failed make Umberto Gori a figure indissolubly linked to the birth and development of International Relations in Italy.